THE DECLINE OF PTOLEMAIC ELEPHANT HUNTING: AN ANALYSIS OF THE CONTRIBUTORY FACTORS*. (16th September 2016) - Cobb, Matthew
Abstract : After the death of Alexander the Great in 323, his successors ( diadochi ) engaged in a series of internecine struggles to take control of the territory he had conquered. One of the most capable of these, Ptolemy, the son of Lagus (later to become Ptolemy I Soter), took control of Egypt, initially as satrap (323–306) and subsequently as king (306–283/282). Over several decades Ptolemy was able to seize Coele-Syria and parts of Asia Minor, and achieved leadership of the League of Islanders in the Aegean. The battles between the successors were fought with sizable infantry and cavalry forces. However, one of the most notable and highly valued components of these military forces were battle elephants.